Wenn alle Teil der Mittelschicht sein wollen: (Fehl-)Wahrnehmungen von Ungleichheit und warum sie für Sozialpolitik wichtig sind; When everyone thinks they're middle-class: (Mis-)Perceptions of inequality and why they matter for social policy - Luna Bellani; Nona Bledow; Marius R. Busemeyer; Guido Schwerdt (University of Konstanz, Cluster of Excellence "The Politics of Inequality", Das Progressive Zentrum e.V., 2021)
Für eine Politik, die auf Wohlstand und soziale Mobilität abzielt, stellt die bestehende soziale und wirtschaftliche Ungleichheit eine anhaltende Herausforderung dar. Dabei wird Ungleichheit in der deutschen Bevölkerung vielfach falsch wahrgenommen: Sie wird zwar durchaus als Problem betrachtet; ihr Ausmaß wird aber in wichtigen Aspekten unterschätzt, wie dieses Papier anhand von Befragungsdaten zeigt. Dabei unterstützen große Teile der Bevölkerung eine egalitärere Gesellschaft. – – Current levels of social and economic inequalities are an enduring challenge for policymakers concerned with sustaining high levels of prosperity and social mobility. Understanding which types of inequalities people in Germany regard as important is crucial. Using survey data, this paper presents evidence that misperceptions about inequality among the German population are common. Inequality is perceived as a problem and most respondents would prefer a more egalitarian society. However, people still underestimate the extent of inequality in important ways. This suggests that there is the potential for a policy agenda that emphasizes progressive and egalitarian policies. For such policies to gain public support, they should be tied to information on specific aspects of inequality.
urn:nbn:de:bsz:352-2-mhwoom1ygp7j7
Keywords: 320